1998
DOI: 10.1046/j.1523-1755.1998.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a capture ELISA for detection of proteinase-3 antineutrophil cytoplasmic antibody: Technical Note

Abstract: Detection of antineutrophil cytoplasmic antibodies (ANCA) has become a useful tool in the diagnosis of Wegener's granulomatosis and microscopic polyangiitis. However, the results obtained with indirect immunofluorescence (IIF) and by ELISA for ANCA demonstration do not always correlate. A possible explanation for this finding could be that proteins are denatured during the process of antigen purification or during coating onto the solid phase. To avoid this possibility, a monoclonal antibody to PR3 that is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 31 publications
3
42
1
4
Order By: Relevance
“…Also MPOhas been expressed in an enzymatically active form which can be used as an antigen for MPO-ANCA determination (35). Recent studies have suggested that it may be advantageous to capture PR3 using a monoclonal antibody, which does not cover up any important epitope on the PR3 molecule (29,30). There maybe two advantages with this approach: 1) the conformation of the molecule may be better preserved, and 2) all epitopes on the PR3 molecule may be available for reaction with PR3-ANCAin human sera.…”
Section: If-anca Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Also MPOhas been expressed in an enzymatically active form which can be used as an antigen for MPO-ANCA determination (35). Recent studies have suggested that it may be advantageous to capture PR3 using a monoclonal antibody, which does not cover up any important epitope on the PR3 molecule (29,30). There maybe two advantages with this approach: 1) the conformation of the molecule may be better preserved, and 2) all epitopes on the PR3 molecule may be available for reaction with PR3-ANCAin human sera.…”
Section: If-anca Testingmentioning
confidence: 99%
“…There maybe two advantages with this approach: 1) the conformation of the molecule may be better preserved, and 2) all epitopes on the PR3 molecule may be available for reaction with PR3-ANCAin human sera. Using capture PR3-ANCA technique it seems possible to see better correlations between PR3-ANCAlevels and disease activity than by use of direct EIA (29,30). There are no indications that capture MPO-ANCA detection is advantageous over the direct EIA technique.…”
Section: If-anca Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). In these ELISA-based tests a monoclonal antibody, specific for either PR3 or MPO, is coated to the carrier and, next, the antigen preparation, either as a crude neutrophil extract (Cohen Tervaert et al, 1990) or as purified antigens (Westman et al, 1998;Boomsma et al, 2001) is added. The antigen is now captured by the monoclonal antibody, hence the name, and the assay is continued with subsequent incubations with patient serum, anti-human IgG conjugate, and, finally, the substrate, similar as in the direct ELISA described above.…”
Section: Methods For Anca Detectionmentioning
confidence: 99%
“…One such assay was almost equivalent in terms of speci¢city and sensitivity to a direct ELISA and IIF assay and another group report that the sensitivity for WG was increased by 50% without compromising speci¢-city. 34,35 Their performance in di¡erent routine laboratory settings is yet to be evaluated fully and such ¢ndings are not universal. 36 It is not only IF tests that may be di⁄cult to interpret in that some SLEs have 'true' P-ANCA on IIF.…”
Section: Laboratory Investigation Of Small Vessel Systemic Vasculitismentioning
confidence: 99%